Herbicides better than manual weeding - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
René Rabezandrina, of the Department of Agriculture of the University of Antananarivo, Madagascar, also shares some ideas on weeds (Spore 72, p.4) : 'True, not all farmers can get hold of some herbicides in isolated areas, but this should not be a...